Improving activities and learning outcomes through the flipped classroom - Nirwana Nirwana; Nurhikmah H; Arnidah Arnidah (Inovasi Kurikulum, 2025)
Learning Indonesian requires diverse learning resources to achieve optimal learning outcomes, especially when utilizing technology in education. To ensure effective learning outcomes, educators should be able to create innovations and select various learning strategies. Choosing the right and effective learning strategy will help students better understand the material. To address these challenges, the researcher implemented the Flipped Classroom strategy assisted by Google Sites, hoping that students would become more active, exchange ideas, and make classroom learning more meaningful. This research aims to analyze the effect of the Flipped Classroom learning strategy, supported by Google Sites, on the activities and learning outcomes of Grade X MIPA 3 students at SMA Negeri 1 Majene. The research method used was experimental research with a Pre-Experimental Design method. The research design was a Pretest-Posttest Design. This study involved two classes: the experimental class, which applied the Flipped Classroom learning strategy, and the control class, which did not use the Flipped Classroom strategy but followed a conventional teaching method. The results showed that the Flipped Classroom learning model, supported by Google Sites, had a positive and significant impact on the Indonesian learning outcomes of Grade XI MIPA 3 students at SMA Negeri 1 Majene.   Abstrak Pembelajaran Bahasa Indonesia membutuhkan sumber belajar yang variatif supaya memperoleh hasil belajar yang optimal terutama dalam pemanfaatan teknologi dalam pembelajaran. Supaya pembelajaran membuahkan hasil yang baik, pendidik seharusnya dapat membuat inovasi baru dan memilih berbagai variasi strategi pembelajaran. Pemilihan strategi pembelajaran yang tepat dan efektif akan membantu peserta didik dalam memahami materi. Mengatasi permasalahan tersebut peneliti menerapkan strategi pembelajaran Flipped Classroom berbantu Google Sites dengan harapan peserta didik dapat menjadi lebih aktif, saling bertukar pendapat sehingga menjadikan pembelajaran dikelas lebih bermakna, Penelitian ini bertujuan untuk menganalisis pengaruh strategi strategi pembelajaran flipped classroom dengan bantuan Google Sites terhadap aktivitas dan hasil belajar peserta didik kelas X MIPA 3 SMA Negeri 1 Majene. Metode penelitian yang digunakan adalah penelitian eksperimen dengan metode Pre-Experiment Design. Desain penelitian yang digunakan adalah Pretest-Posttest Design. Penelitian ini melibatkan dua kelas, yaitu kelas eksperimen yang menerapkan strategi pembelajaran flipped classroom dan kelas yang tidak menerapkan strategi pembelajaran flipped classroom atau dengan metode konvensional. Hasil penelitian menunjukkan bahwa ada pengaruh model pembelajaran flipped classroom dengan bantuan aplikasi google sites yang positif dan signifikan terhadap hasil belajar Bahasa Indonesia pada peserta didik kelas XI MIPA 3 SMA Negeri 1 Majene. Kata Kunci: flipped classroom; hasil belajar; strategi pembelajaran inovatif